El rol de la mujer en espacios de docencia y cargos directivos en instituciones de educación superior: estudio de caso de la Universidad Central del Ecuador (2010-2020) [Investigaciones] - Ponce Tituaña, Lizbeth Gisselle (2022)
The social configuration and the legal system have limited the presence of women in the teaching and management staff of the Central University of Ecuador from the 2010-2010 academic period until the 2019-2020 academic period. On the other hand, the social-feminist movements and women’s collectives have raised theses claiming the right of women to participate and be part of educational spaces under conditions of equality and non-discrimination. This work objective was to investigate why the number of women at the Central University of Ecuador has increased. The methodology used was the quali-quantitative approach that allowed statistical data analysis from twenty academic periods of the Faculties of Medical Sciences, Engineering and Applied Sciences, Jurisprudence, Political and Social Sciences, and Philosophy.